Exploring Heterogeneity of Distribution Intensity: Evidence from Emerging Market Entry Experience with Benchmark Brands in China - Chang, Shun-Chuan; Tang, Ying-Chan (Asian Journal of Empirical Research, 2015)
As most mature markets enter the fray, emerging markets in Asia offer an opportunity for global brands to embrace. One of the critical decisions for these firms is how many intermediaries should be used in emerging markets. Although determinants affecting market entry and distribution intensity have been proposed by the literature, emerging market background and channel setting context could be drastically different. This study empirically examines four benchmark brands, Nokia, HP, Haier, and Lenovo in China’s 3Cs (computer, communication, and consumer electronics) distributors. Our research contributes to summarize important findings for the radically competitive market. First, several concentration measures reveal unobserved nature of heterogeneous distribution intensity. Second, the interaction of CDI (category development index) and BDI (brand development index) in representing development of distribution channels is clarified. Third, linking the unobserved heterogeneity of distribution intensity, the Gamma-Poisson mixture, NBD regression modeling covariate effects on market growth, distribution capability, and brand power based on CDI and BDI could be investigated. The results contribute to a gear drive mechanism applicable for generating distribution intensities among different cities in emerging markets.